Community based bioremediation: grassroots responses to urban soil contamination - Kellogg, Scott (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
The past 150 years of industrial processes have left a legacy of toxicity in the soils of today’s urban environments. Exposure to soil based pollutants disproportionately affects low-income communities who are frequently located within formerly industrialized zones. Both gardeners, who come into direct contact with soil, as well as those who eat the products grown in the soil, are at risk to exposure from industrial contaminants. Options for low-income communities for remediating contaminated soils are limited, with most remediation work being carried out by costly engineering firms. Even more problematic is the overall lack of awareness and available information regarding safety and best practices with soils. In response to these challenges, a grassroots movement has emerged that seeks to empower urban residents with the tools and information necessary to address residual industrial toxicity in their ecosystems. Focusing on methods that are simple and affordable, this movement wishes to remove the barriers of cost and technical expertise that may be otherwise prohibitive. This paper will give an overview of this exemplar of generative justice, looking at case studies of organizations that have been successful in implementing these strategies.